Pharmacogenetics in Psychiatry: Perceived Value and Opinions in a Chilean Sample of Practitioners - Undurraga, Juan; Bórquez-Infante, Ignacio; Crossley, Nicolás A.; Prieto, Miguel L.; Repetto, Gabriela M. (Frontiers in Pharmacology, 2021)
Use of pharmacogenetics (PGx) testing to guide clinical decisions is growing in developed countries. Published guidelines for gene-drug pair analysis are available for prescriptions in psychiatry, but information on their utilization, barriers and health outcomes in Latin America is limited. This work aimed at identifying current use, opinions and perceived obstacles on PGx testing among psychiatrists in Chile, via an online, anonymous survey. Among 123 respondents (5.9% of registered psychiatrists in the country), 16.3% reported ever requesting a PGx test. The vast majority (95%) was ordered by clinicians practicing in the Metropolitan Region of Santiago. Having more than 20 years in practice was positively associated with prior use of PGx, (OR 3.74 (1.19-11.80)), while working in the public health system was negatively associated (OR 0.30 (0.10 - 0.83)). Perceived barriers to local implementation included insufficient evidence of clinical utility, limited clinicians´ knowledge on PGx and test availability, and health systems´ issues, such as costs and reimbursement. Despite the recognition of these barriers, 80% of respondents asserted that it is likely that they will incorporate PGx tests in their practice in the next five years. Given these results, we propose next steps to facilitate pertinent implementation such as further research in health outcomes and clinical utility of known and novel clinically actionable variants, growth in local sequencing capabilities, education of clinicians, incorporation of clinical decision support tools and economic evaluations in local context.